Testicular tissue cryopreservation and transplantation as a strategy for feline conservation: a review of research advances - Han, Zhiqiang; Liu, Xin; Wang, Haijun; Qazi, Izhar Hyder; Wang, Luyao; Du, Rui; Dai, Xiangpeng; Xu, Chao (Frontiers in Veterinary Science, 2025)
As we humans continue our detrimental activities on the planet, the biodiversity loss is now seen as a big threat to entire ecosystem in which we all live. This issue becomes even more critical as we see a rapid increase in the number of animal species being listed as endangered, and a far greater rate of species extinction. We all know that felines play a crucial part in our ecosystems, it is therefore safe to argue that their conservation could play an important role in minimizing the biodiversity loss. Advanced reproductive biotechnologies including testicular tissue cryopreservation and transplantation are considered as effective tools for the conservation of animal species. As we have seen with the Giant Panda, these biotechnologies could offer new possibilities for the conservation of other endangered species including felines. Although previously a few wild feline spp. were conserved by this method, little is known about the factors influencing the efficiency of these methods. Therefore, if we are to maximize the conservation efforts, further optimization of these biotechnologies is required to achieve better conservation results. In this article, we present an overview of testicular tissue of felines and the factors influencing testicular tissue cryopreservation and testicular graft recovery in felines.